Synthesis of novel quinoline-thiazolobenzimidazolone hybrids as anticancer agents through caspase-dependent apoptosis - Bouria, Houria; Alliouche, Hayette; Chouiter, Mohamed Imed; Belfaitah, Ali; Pacheco, Teresa; Gala, Viktor; Pereira, David; Silva, Artur M S (Future medicinal chemistry, 2025)
AIM: This work explores the synthesis of new bi-heterocyclic hybrid compounds based on quinoline ring and investigates their potential as anticancer agents. MATERIALS & METHODS: The novel fused quinoline-thiazolo[3,2-a] benzimidazole-3(2 h)one hybrids were prepared by regioselective nucleophilic ring opening of the corresponding quinolinyl-oxiranes. In vitro cytotoxic activity was evaluated against human lung (A549) and gastric (AGS) cancer cell lines. RESULTS: Global results showed that all tested compounds have promising inhibitory properties. Compounds 17 and 18 bearing two methoxy groups on the quinoline ring have exhibited remarkable and interesting activities. The investigation of the cell death process showed that these compounds activated a caspase-dependent apoptosis pathway. Results were further supported by molecular docking studies. CONCLUSION: Both compounds exhibited good drug-like characteristics, which make them promising drug candidates.
Keywords: Drug Screening Assays, Antitumor; Humans; molecular docking; simulace molekulového dockingu; Structure-Activity Relationship; kaspasy; vztahy mezi strukturou a aktivitou; hybrid compounds; Benzimidazoles; Molecular Docking Simulation; Antineoplastic Agents; Quinolines; epoxide ring opening; lidé; proliferace buněk; Caspases; Thiazolobenzimidazole; cytotoxic activity; molekulární struktura; benzimidazoly; apoptóza; Molecular Structure; thiazoly; Cell Proliferation; Quinoline; screeningové testy protinádorových léčiv; nádorové buněčné linie; protinádorové látky; Caspase-3; Thiazoles; Cell Line, Tumor; Apoptosis; chinoliny